HIV as a Chronic Illness: Identity Incorporation and Learning - Lisa M. Baumgartner; Keegan N. David (Adult Education Research Conference, 2008)
Abstract: The purpose of this session is twofold: (1) to review tentative findings of a study-in-progress concerning the identity incorporation process and learning of people living with HIV as a chronic illness and (2) to explore issues encountered in conducting research with the chronically ill.
Keywords: HIV; chronic illness; identity; learning